Incentives and Risk Sharing in a Stock Market Equilibrium - Martine Quinzii; Michael Magill (University of California, Department of Economics, 1996)
Economists hold two opposing views of the stock market: one focuses on the negative effect on incentives of separating ownership and control, the other emphasizes its beneficial role for risk sharing. Using a generalization of Diamond''s model which incorporates the effect of entrepreneurial incentives, we show how these two views can be reconciled. We introduce the concept of a stock market equilibrium with rational competitive price perceptions (RCPP) and show that such and equilibrium leads to a constrained optimal trade-off between risk sharing and incentives. We give examples showing the difference between RCPP equilibria and the standard CAPM type equilibria of finance.
Keywords: 330